Fiscal policies during the Covid-19 crisis in Austria: A macroeconomic assessment - Klaus Weyerstrass (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
This EconPol Policy Report assesses the macroeconomic impact of fiscal policy measures introduced by the Austrian government during the Covid-19 crisis in 2020 and 2021. Large parts of the stimulus package aimed at stabilizing companies, employment and private households. According to the study short-term work schemes were particularly successful. Equally effective were measures supporting companies and the self-employed who were directly affected by the containment measures, e.g. liquidity support (fixed cost subsidies and loss compensations), tax reductions and tax deferrals. While support to private consumption generally is not the recommended fiscal policy reaction to a recession which is caused by government measures to restrict consumption possibilities, support to companies, employees and the self-employed who are affected by the closure of some businesses are appropriate, according to the study. At the same time, those companies that would have left the market anyway should not kept alive articifially, as this would hamper structural change. For the same reason, short-time work schemes should only be offered as long as the contaiment measures or other pandemic-related problems such as supply-chain disruptions prevail.
Keywords: 330